Critical care ultrasound - Lumb, Philip; Karakitsos, Dimitrios (Philadelphia, PA Elsevier Saunders, 2015)
For physicians and nurses in critical care medicine, the increased demand and use of ultrasound necessitates further training. Critical Care Ultrasound helps meet that need. A straightforward, practical approach, an abundance of detailed ultrasound images, and online video demonstrations provide step-by-step guidance on the principles and effective use of this important imaging modality in both diagnosis and assistance with specific procedures. Coverage includes the latest applications of ultrasound for neurologic critical care; vascular problems; chest; hemodynamic monitoring; and abdominal and emergency uses, as well as assistance in a variety of specific procedures in critical care medicine.--
"ExpertConsult.com"--Cover.
Includes index.
Keywords: Critical care medicine; Diagnostic ultrasonic imaging; Ultrasonography; Critical Care; Critical care medicine; Diagnostic ultrasonic imaging